Awareness of gestational diabetes mellitus among antenatal women in a primary health center in South India - Vanishree Shriraam; Shriraam M Rani; B. W. C Sathiyasekaran; Shriraam Mahadevan (Indian Journal of Endocrinology and Metabolism, 2013)
Background: Gestational diabetes mellitus (GDM) is a perfect window of opportunity for the prevention of DM in two generations, and its incidence is increasing in our country. Awareness of the condition among antenatal women will translate into prevention and early diagnosis of the disease. This study was done to determine the awareness of GDM among all the antenatal women who attend a Primary Health Center (PHC) for antenatal care. Materials and Methods: A pretested questionnaire consisting of details on background characteristics, 12 questions focusing on Type 2 DM and GDM, and a question on the source of knowledge was administered to all women attending the antenatal clinic. Their responses were scored and the women were graded as having good, fair, or poor knowledge about GDM. Results: One hundred and twenty antenatal women participated in the study. Mean age of the women was 23.8 years (SD: 2.94). Overall, 17.5% women had good knowledge, 56.7% had fair knowledge, and 25.8% women had poor knowledge about GDM. The major sources of awareness of GDM were reported to be television/radio, neighbors/friends, and family members. Discussion: Only a small proportion of rural antenatal women had good knowledge about GDM. The awareness that untreated GDM may pose a risk to the unborn child was high among the study women. Health care workers have to play a greater role in bringing about awareness about GDM among antenatal women.